A kind of rice straw fiber aerogel for uranium adsorption and preparation method thereof

AO-Dex@CS-RSFs aerogel prepared by combining straw fiber with dextran, chitosan and 2-hydroxybenzaldehyde oxime, the existing uranium adsorbents have low mechanical strength and antibacterial properties in marine environments. The poor problem achieves higher uranium absorption efficiency and longer service life.

CN118949864BActive Publication Date: 2025-02-14HAINAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411384408.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-02-14
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The existing uranium adsorbents have low mechanical strength, poor antibacterial properties and average hydrophilic properties in complex marine environments, resulting in the impact of structural stability and uranium absorption efficiency under wave impact and bacterial erosion.

Method used

Using straw fiber as the skeleton support, AO-Dex@CS-RSFs aerogel was prepared by combining with materials such as dextran, chitosan and 2-hydroxybenzaldehyde oxime to improve its mechanical strength, antibacterial and hydrophilic properties. .

Benefits of technology

It improves the mechanical strength and antibacterial properties of the aerogel, enhances its stability and uranium absorption efficiency in the marine environment, extends its service life, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118949864B_ABST
    Figure CN118949864B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of uranium adsorption, and specifically relates to a straw fiber aerogel for uranium adsorption and a preparation method thereof. The preparation method of the straw fiber aerogel includes pretreatment, preparation of Dex@CS-RSFs aerogel and preparation of AO-Dex@CS-RSFs aerogel. The aerogel of the present invention uses straw fiber, a natural material with biodegradability, as a skeleton support, so that the compression strength of the aerogel reaches 8.22MPa, which helps to enhance the structural stability and service life of the aerogel; the introduction of chitosan and dextran gives it excellent antibacterial activity and hydrophilic properties; small molecule oxime-loaded AO-Dex@CS-RSFs aerogel improves the chelation of uranyl by the adsorbent, thereby improving its uranium absorption efficiency. In addition, compared with fibers manufactured by complex spinning technology, the aerogel containing straw fibers of the present invention is more advantageous in terms of environmental protection, low cost and large-scale manufacturing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of uranium adsorption, and particularly relates to a straw fiber aerogel for uranium adsorption and a preparation method thereof. Background Art

[0002] With the rapid growth of population and the continuous acceleration of industrialization, energy consumption is increasing worldwide, and the supply of traditional fossil fuels is facing tremendous pressure. In addition, with the frequent occurrence of global extreme climate disasters in recent years, people have also begun to realize that the climate change caused by traditional fossil fuels is becoming increasingly severe. Therefore, under the dual pressure of energy shortage and climate change, the world is working hard to promote the integration of clean energy into the global energy structure. As a major energy consumer, China's energy system is also heavily dependent on traditional fossil fuels such as coal, oil and natural gas. After the two major development goals of "carbon peak" and "carbon neutrality" are proposed, China's energy structure will gradually transform towards clean and low-carbon development. Nuclear energy, as a mature clean energy, has the characteristics of economic efficiency and environmental friendliness, and plays an important role in protecting the ecological environment and responding to climate change. As the most important nuclear fuel for nuclear power operation, the long-term and sufficient supply of uranium resources is the key to ensuring the sustainable development of my country's nuclear power and an important means to solve the problem of energy shortage.

[0003] However, terrestrial uranium resources are unevenly distributed on the earth. Compared with the terrestrial uranium resource reserves of other countries in the world, my country's terrestrial uranium resources are relatively scarce and extremely difficult to mine, which is difficult to meet the needs of the stable and sustainable development of my country's nuclear power industry. Therefore, finding a new uranium resource for continuous supply has become an urgent problem to be solved in my country. There are a large amount of uranium resources in the ocean, which is about 1,000 times the amount of uranium deposited on land. As a major maritime country, my country has a vast sea area. How to efficiently extract uranium resources from the ocean and find a low-cost uranium adsorption technology will become an important starting point for my country to solve the shortage of terrestrial uranium resources. Although there are abundant uranium resources in the ocean, the marine environment is extremely complex and the technology is still not mature enough. It faces many challenges, which are mainly reflected in the following aspects: First, the concentration of uranium in seawater is low and coexists with a variety of high-concentration interfering ions. Second, the impact of waves and ocean currents will destroy the structure of the adsorbent, reduce the mechanical strength, and shorten the service life. Third, there are a large number of bacteria in the real marine environment. These bacteria will grow and reproduce on the surface of the adsorbent, interfering with the adsorption efficiency of the adsorbent in seawater. If these challenges can be overcome, it will be of great significance to the practical application of adsorbents. Therefore, it is urgent to develop adsorbents with good mechanical strength to withstand the impact of waves in complex marine environments and enhance the service life of adsorbents. At the same time, the adsorbents must also have good antibacterial properties, hydrophilic properties, and chelating ligands to prevent bacteria from growing and multiplying on the surface of the adsorbent, and have good hydrophilicity and uranyl chelating ability to improve the adsorption efficiency of uranium. Summary of the invention

[0004] The purpose of the present invention is to overcome the disadvantages of the prior art and provide a straw fiber aerogel for uranium adsorption and a preparation method thereof.

[0005] The object of the present invention is achieved by the following technical scheme: A method for preparing straw fiber aerogel for uranium adsorption, which comprises the following steps:

[0006] S1. Pretreatment: adding straw fiber debris to a sodium hydroxide solution, treating at 120-180°C for 2-12h, recovering solid fibers after the reaction, and adding the solid fibers to an acetic acid solution for dispersion to obtain a straw fiber suspension;

[0007] S2. Preparation of Dex@CS-RSFs aerogel: Dextran and chitosan were added to the straw fiber suspension, and after mixing evenly, a cross-linking agent, polyethylene glycol diglycidyl ether, was added and stirred for 0.5 to 6 hours. The reaction solution was poured into a mold and freeze-dried to obtain Dex@CS-RSFs aerogel;

[0008] S3. Preparation of AO-Dex@CS-RSFs aerogel: Add 2-hydroxybenzaldehyde oxime solution to Dex@CS-RSFs aerogel and stir for 50 to 70 minutes. Then add cross-linking agent polyethylene glycol diglycidyl ether and cross-link for 2.5 to 3.5 hours to obtain AO-Dex@CS-RSFs aerogel.

[0009] Furthermore, the concentration of the sodium hydroxide solution in step S1 is 2-10 mol / L, and the volume ratio of the mass of the straw fiber fragments to the sodium hydroxide solution is 1 g:50-70 mL.

[0010] Furthermore, the dispersion in step S1 is performed by ultrasonic dispersion, the concentration of the acetic acid solution is 1-5wt%, and the mass volume ratio of the solid fiber to the acetic acid solution is 1g:25-35mL.

[0011] Furthermore, in step S2, the volume ratio of the total mass of the dextran and chitosan to the straw fiber suspension is 6-30 mg:1 mL, the mass ratio of the dextran and chitosan is 1:2-5, and the volume ratio of the cross-linking agent to the straw fiber suspension is 0.1-0.8:60.

[0012] Furthermore, the concentration of the 2-hydroxybenzaldehyde oxime solution in step S3 is 2 to 10 mg / mL, the volume ratio of the mass of the Dex@CS-RSFs aerogel to the 2-hydroxybenzaldehyde oxime solution is 1.2 to 2.0 mg:1 mL, and the volume ratio of polyethylene glycol diglycidyl ether to the 2-hydroxybenzaldehyde oxime solution is 0.03 to 0.15:100.

[0013] The straw fiber aerogel for uranium adsorption prepared by the above method

[0014] In the present invention:

[0015] (1) Existing uranium adsorbents have low mechanical strength and are difficult to maintain good stability in uranium adsorption solutions. The present invention uses straw fiber, a natural material with good biodegradability, as a skeleton support to improve the mechanical strength of the adsorbent, so that it can maintain good structural stability during the uranium adsorption process, extend the service life of the adsorbent, and has good application prospects.

[0016] (2) The antibacterial properties of the uranium adsorbents reported so far are poor. Bacteria in the water reproduce on the surface of the adsorbent, blocking the adsorption sites and interfering with the uranium adsorption efficiency of the adsorbent. The present invention introduces the biomass material chitosan to improve the antibacterial properties of the adsorbent and prevent marine microorganisms from growing and multiplying on the surface of the adsorbent material, thereby improving the uranium adsorption efficiency. At the same time, 2-hydroxybenzaldehyde oxime is introduced as a uranium adsorption ligand to enhance the chelation of uranyl, thereby further increasing the uranium adsorption amount.

[0017] (3) The hydrophilicity of conventional uranium adsorbents is average, which results in the ineffective contact between the uranium solution and the adsorbent ligand, thus affecting the adsorption efficiency. The present invention introduces high molecular weight dextran to give the adsorbent good hydrophilicity, allowing the uranium solution to better contact the adsorbent, and increasing the transmission rate of the uranium solution inside the adsorbent, thereby improving the uranium adsorption efficiency.

[0018] The present invention has the following advantages: the present invention discloses a straw fiber aerogel for uranium adsorption. The AO-Dex@CS-RSFs aerogel uses the biodegradable natural material straw fiber as the skeleton support, so that the compression strength of the aerogel reaches 8.22MPa, which helps to enhance the structural stability and service life of the aerogel; at the same time, chitosan and dextran are introduced into the straw fiber aerogel. Through antibacterial experiments and hydrophilicity tests, it is proved that the AO-Dex@CS-RSFs aerogel has excellent antibacterial activity and hydrophilicity, which helps to protect the adsorption site and promote the adsorption of uranium. In addition, compared with most aerogel adsorbents, the small molecule oxime-loaded AO-Dex@CS-RSFs aerogel improves the chelation of the adsorbent to uranyl, thereby improving its uranium adsorption efficiency. More importantly, compared with the fibers manufactured by complex spinning technology, the AO-Dex@CS-RSFs aerogel containing straw fibers is more advantageous in terms of environmental protection, low cost and large-scale manufacturing. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a physical picture of AO-Dex@CS-RSFs aerogel prepared by the method of the present invention.

[0020] Figure 2 This is a microstructure diagram of AO-Dex@CS-RSFs aerogel prepared by the method of the present invention.

[0021] Figure 3 This is a graph showing the test results of the uranium adsorption performance of the AO-Dex@CS-RSFs aerogel prepared by the method of the present invention. In the graph, a is the uranium adsorption performance within different pH ranges, and b is the kinetic test result.

[0022] Figure 4 This is a graph showing the XPS analysis results of the AO-Dex@CS-RSFs aerogel prepared by the method of the present invention after uranium adsorption. In the graph, a is the full XPS spectrum of the AO-Dex@CS-RSFs aerogel after uranium adsorption, and b is the peak fitting of the XPS high-resolution spectrum in the U 4f region.

[0023] Figure 5 This is a graph showing the stress-strain curve (mechanical properties) test results of the AO-Dex@CS-RSFs aerogel prepared by the method of the present invention.

[0024] Figure 6 This is a graph showing the antibacterial performance test results of AO-Dex@CS-RSFs aerogel prepared by the method of the present invention.

[0025] Figure 7 The dynamic water contact angle test results of AO-Dex@CS-RSFs aerogel prepared by the method of the present invention. DETAILED DESCRIPTION

[0026] The present invention is further described below in conjunction with the accompanying drawings and embodiments. The protection scope of the present invention is not limited to the following: Embodiment 1: A method for preparing a straw fiber aerogel, which comprises the following steps:

[0027] S1. Pretreatment: The straw fiber debris was added to a 2 mol / L sodium hydroxide solution, the mass of the straw fiber debris and the volume ratio of the sodium hydroxide solution was 1 g: 50 mL, and the reaction was carried out at 120 ° C for 12 h. After the reaction was completed, the solid fiber was recovered and added to a 1 wt% acetic acid solution using ultrasound for dispersion. The mass volume ratio of the solid fiber to the acetic acid solution was 1 g: 25 mL to obtain a straw fiber suspension;

[0028] S2. Preparation of Dex@CS-RSFs aerogel: dextran and chitosan were added to the straw fiber suspension, and after mixing, a cross-linking agent, polyethylene glycol diglycidyl ether, was added and stirred for 6 hours. The reaction solution was poured into a mold and freeze-dried to obtain Dex@CS-RSFs aerogel; wherein the volume ratio of the total mass of the dextran and chitosan to the straw fiber suspension was 6 mg:1 mL, the mass ratio of the dextran and chitosan was 1:2, and the volume ratio of the cross-linking agent to the straw fiber suspension was 0.1:60;

[0029] S3. Preparation of AO-Dex@CS-RSFs aerogel: A 2-hydroxybenzaldehyde oxime solution with a concentration of 2 mg / mL was added to the Dex@CS-RSFs aerogel, and the volume ratio of the mass of the Dex@CS-RSFs aerogel to the 2-hydroxybenzaldehyde oxime solution was 1.2 mg:1 mL. The mixture was stirred for 70 min, and then the cross-linking agent polyethylene glycol diglycidyl ether was added for cross-linking for 3.5 h. The volume ratio of polyethylene glycol diglycidyl ether to the 2-hydroxybenzaldehyde oxime solution was 0.03:100 to obtain AO-Dex@CS-RSFs aerogel.

[0030] Embodiment 2: A method for preparing a straw fiber aerogel, comprising the following steps:

[0031] S1. Pretreatment: The straw fiber debris was added to a 10 mol / L sodium hydroxide solution, the mass of the straw fiber debris and the volume ratio of the sodium hydroxide solution was 1 g: 70 mL, and the reaction was performed at 180 ° C for 2 h. After the reaction was completed, the solid fiber was recovered and added to a 5 wt % acetic acid solution and dispersed by ultrasound. The mass volume ratio of the solid fiber to the acetic acid solution was 1 g: 35 mL to obtain a straw fiber suspension;

[0032] S2. Preparation of Dex@CS-RSFs aerogel: dextran and chitosan were added to the straw fiber suspension, and after mixing, a cross-linking agent, polyethylene glycol diglycidyl ether, was added and stirred for reaction for 0.5 h. The reaction solution was poured into a mold and freeze-dried to obtain Dex@CS-RSFs aerogel; wherein the volume ratio of the total mass of the dextran and chitosan to the straw fiber suspension was 30 mg:1 mL, the mass ratio of the dextran and chitosan was 1:5, and the volume ratio of the cross-linking agent to the straw fiber suspension was 0.8:60;

[0033] S3. Preparation of AO-Dex@CS-RSFs aerogel: A 2-hydroxybenzaldehyde oxime solution with a concentration of 10 mg / mL was added to the Dex@CS-RSFs aerogel, and the volume ratio of the mass of the Dex@CS-RSFs aerogel to the 2-hydroxybenzaldehyde oxime solution was 2.0 mg:1 mL. Stir for 70 minutes, and then add the cross-linking agent polyethylene glycol diglycidyl ether for cross-linking for 2.5 hours. The volume ratio of polyethylene glycol diglycidyl ether to the 2-hydroxybenzaldehyde oxime solution was 0.15:100 to obtain AO-Dex@CS-RSFs aerogel.

[0034] Embodiment 3: A method for preparing a straw fiber aerogel, comprising the following steps:

[0035] S1. Pretreatment: The straw fiber debris was added to a sodium hydroxide solution having a concentration of 6 mol / L, the mass of the straw fiber debris and the volume ratio of the sodium hydroxide solution was 1 g: 60 mL, and the reaction was performed at 150 ° C for 6 h. After the reaction was completed, the solid fiber was recovered and added to an acetic acid solution having a concentration of 3 wt % and dispersed by ultrasound. The mass volume ratio of the solid fiber to the acetic acid solution was 1 g: 28 mL to obtain a straw fiber suspension;

[0036] S2. Preparation of Dex@CS-RSFs aerogel: dextran and chitosan were added to the straw fiber suspension, and after mixing, a cross-linking agent, polyethylene glycol diglycidyl ether, was added and stirred for reaction for 3 hours. The reaction solution was poured into a mold and freeze-dried to obtain Dex@CS-RSFs aerogel; wherein the volume ratio of the total mass of the dextran and chitosan to the straw fiber suspension was 20 mg:1 mL, the mass ratio of the dextran and chitosan was 1:3, and the volume ratio of the cross-linking agent to the straw fiber suspension was 0.4:60;

[0037] S3. Preparation of AO-Dex@CS-RSFs aerogel: A 5 mg / mL 2-hydroxybenzaldehyde oxime solution was added to the Dex@CS-RSFs aerogel, and the volume ratio of the mass of the Dex@CS-RSFs aerogel to the 2-hydroxybenzaldehyde oxime solution was 1.8 mg:1 mL. Stir for 58 min, and then add the cross-linking agent polyethylene glycol diglycidyl ether for cross-linking for 3 h. The volume ratio of polyethylene glycol diglycidyl ether to the 2-hydroxybenzaldehyde oxime solution was 0.1:100 to obtain AO-Dex@CS-RSFs aerogel.

[0038] The beneficial effects of the present invention are described below by experiments:

[0039] 1. Preparation of AO-Dex@CS-RSFs aerogel

[0040] S1. Pretreatment: 1 g of rice straw fibers (RSFs) were cut into pieces and added into 60 mL of 5 M sodium hydroxide solution, and then hydrothermally reacted at 150°C for 6 h. After the reaction was completed, the solid fibers were washed with water and separated and recovered. The solid fibers were dispersed into 30 mL of 2% acetic acid solution under the action of ultrasound to produce a uniform rice straw fiber suspension.

[0041] S2. Preparation of Dex@CS-RSFs aerogel: 60 mg of dextran and 300 mg of chitosan were combined with the straw fiber suspension obtained in the previous step, and mixed by ultrasound and stirring to obtain a uniform Dex@CS-RSFs suspension. Then, 200 μL of polyethylene glycol diglycidyl ether was added as a crosslinker, mixed and stirred for 1 h, and the suspension was poured into a mold and freeze-dried for 48 h to obtain Dex@CS-RSFs aerogel.

[0042] S3. Preparation of AO-Dex@CS-RSFs aerogel: The volume was 100 mL, the concentration was 5 mg / mL 2-hydroxybenzaldehyde oxime, the Dex@CS-RSFs aerogel obtained in the previous step was placed in it, stirred for 1 hour, and then 50 μL of polyethylene glycol diglycidyl ether was added and stirred for cross-linking for 3 hours to obtain AO-Dex@CS-RSFs aerogel. The actual photo is shown in Figure 1 .

[0043] 2. Microstructure of the sample

[0044] The AO-Dex@CS-RSFs aerogel prepared in 1 was scanned by electron microscope. Figure 2 The figure shows the microstructure of AO-Dex@CS-RSFs aerogel. The SEM results show that the aerogel has a lamellar structure with an average distance of about 40 μm between the lamellar structures. This structure is conducive to the entry of uranyl ions in seawater into the aerogel. It can also be observed that the straw fibers are cross-linked in the lamellar structure as a skeleton support, which strengthens the interaction between them and forms a whole, thus improving the mechanical strength of the aerogel.

[0045] 3. Uranium extraction performance

[0046] The straw fiber aerogel prepared in 1 was subjected to uranium adsorption test, and the test results are as follows Figure 3 As shown, Figure 3 a reflects the adsorbent The uranium extraction performance in different pH ranges in simulated seawater is shown in the simulation with the optimal pH = 5 and the initial uranium concentration of 16 ppm. seawater The uranium extraction amount reached a peak value (265±2.0mg-U / g-Ads); and kinetic tests were carried out such as Figure 3As shown in Figure 2, the uranium adsorption in simulated seawater containing uranium at concentrations of 4, 8, and 16 reached saturation in a very short time, and the saturated adsorption reached 105.8, 177.7, and 260.8 mg-U / g-Ads, respectively. Importantly, the main adsorption process was completed in just 3 hours, at which time the adsorption reached 87.24%, 91.90%, and 92.52% of the saturated adsorption, respectively.

[0047] 4.XPS analysis

[0048] The AO-Dex@CS-RSFs aerogel prepared in 1 was subjected to XPS analysis after uranium adsorption. Figure 4 As shown, Figure 4 a shows the XPS spectrum of AO-Dex@CS-RSFs aerogel after uranium adsorption. The U 4f peak appears in the XPS spectrum, indicating the presence of uranium on the adsorbent. Figure 4 b is the peak fitting of the high-resolution spectrum of U 4f. The results show that: U 4f 7 / 2 Three peaks can be distinguished at 381.86, 383.26, and 385.82 eV, U 4f 5 / 2 Peaks can be separated at 392.73 and 393.49 eV. These results are consistent with the XPS peak separation results of the reported oxime-based adsorbent after uranium adsorption, confirming that oxime and UO2 2+ In addition, in the experiment, we also observed that the color of the aerogel changed from milky white to yellow due to the adsorption of uranium. These results show that the adsorbent can indeed adsorb uranium well.

[0049] 5. Mechanical properties

[0050] The AO-Dex@CS-RSFs aerogel prepared in 1 was compressed to test its mechanical properties. Figure 5 As shown, the stress-strain curve of AO-Dex@CS-RSFs aerogel demonstrates the excellent mechanical properties of the aerogel, and its maximum compressive strength is 8.22MPa.

[0051] 6. Antibacterial properties

[0052] The antibacterial properties of AO-Dex@CS-RSFs aerogel prepared in 1 were tested by the inhibition zone experiment. Figure 6As shown, AO-Dex@CS-RSFs aerogel has good antibacterial properties against four typical bacteria, namely Staphylococcus aureus (Gram-positive bacteria), Escherichia coli (Gram-negative bacteria), Vibrio alginolyticus (marine bacteria) and Bacillus subtilis (widely used in aquaculture environments). The inhibition zones of AO-Dex@CS-RSFs aerogel against the four typical bacteria are 13.19±0.37, 13.75±0.42, 17.01±0.12 and 14.86±0.26 mm, respectively. The introduction of chitosan gives the aerogel antibacterial ability, which can prevent bacteria and other microorganisms in the water from clogging its adsorption sites to protect the adsorption sites.

[0053] 7. Hydrophilicity

[0054] The hydrophilicity of the AO-Dex@CS-RSFs aerogel prepared in 1 was tested. Figure 7 As shown, Figure 7 The dynamic water contact angle of AO-Dex@CS-RSFs aerogel is shown. At t=0.012s, the water contact angle is 40°, which indicates that the material has good hydrophilicity; at t=0.018s, the water droplet is basically penetrated, indicating that the material has high porosity and good connectivity; at t=0.081s, the water droplet is completely penetrated (the water contact angle reaches 0°), indicating that the material has good wetting properties and can accelerate the contact efficiency with uranyl ions in the solution.

[0055] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which are all covered by the protection scope of the present invention.

Claims

1. A method for preparing straw fiber aerogel for uranium adsorption, characterized in that: It includes the following steps: S1. Pretreatment: adding straw fiber debris to a sodium hydroxide solution, treating at 120-180°C for 2-12h, recovering solid fibers after the reaction, and adding the solid fibers to an acetic acid solution for dispersion to obtain a straw fiber suspension; S2. Preparation of Dex@CS-RSFs aerogel: Dextran and chitosan were added to the straw fiber suspension, and after mixing evenly, a cross-linking agent, polyethylene glycol diglycidyl ether, was added and stirred for 0.5 to 6 hours. The reaction solution was poured into a mold and freeze-dried to obtain Dex@CS-RSFs aerogel; S3. Preparation of AO-Dex@CS-RSFs aerogel: Add 2-hydroxybenzaldehyde oxime solution to Dex@CS-RSFs aerogel and stir for 50 to 70 minutes. Then add cross-linking agent polyethylene glycol diglycidyl ether and cross-link for 2.5 to 3.5 hours to obtain AO-Dex@CS-RSFs aerogel.

2. The method for preparing a straw fiber aerogel for uranium adsorption according to claim 1, characterized in that: The concentration of the sodium hydroxide solution in step S1 is 2-10 mol / L, and the volume ratio of the mass of the straw fiber fragments to the sodium hydroxide solution is 1 g:50-70 mL.

3. The method for preparing a straw fiber aerogel for uranium adsorption according to claim 1, characterized in that: The dispersion in step S1 is performed by ultrasonic dispersion, the concentration of the acetic acid solution is 1-5wt%, and the mass volume ratio of the solid fiber to the acetic acid solution is 1g:25-35mL.

4. The method for preparing a straw fiber aerogel for uranium adsorption according to claim 1, characterized in that: In step S2, the volume ratio of the total mass of the dextran and chitosan to the straw fiber suspension is 6-30 mg:1 mL, the mass ratio of the dextran and chitosan is 1:2-5, and the volume ratio of the cross-linking agent to the straw fiber suspension is 0.1-0.8:

60.

5. The method for preparing a straw fiber aerogel for uranium adsorption according to claim 1, characterized in that: The concentration of the 2-hydroxybenzaldehyde oxime solution in step S3 is 2-10 mg / mL, the volume ratio of the mass of the Dex@CS-RSFs aerogel to the 2-hydroxybenzaldehyde oxime solution is 1.2-2.0 mg:1 mL, and the volume ratio of polyethylene glycol diglycidyl ether to the 2-hydroxybenzaldehyde oxime solution is 0.03-0.15:

100.

6. A rice straw fiber aerogel for uranium adsorption prepared by the method according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Preparation method and application of three-dimensional porous algae-based / chitosan aerogel used for uranium-bearing wastewater treatment

    CN110026137A

  • Chitosan-based covalent organic framework aerogel material as well as preparation method and application thereof

    CN114570296A